Valuation of kelp forest ecosystem services in the Falkland Islands: A case study integrating blue carbon sequestration potential - Bayley, Daniel; Brickle, Paul; Brewin, Paul; Golding, Neil; Pelembe, Tara (One ecosystem : ecology and sustainability data journal, 2021)
Kelp forests provide many important ecosystem services to people, including mitigating storm damage, cycling nutrients, and providing commercially-harvestable resources. However, kelp forests’ ability to sequester carbon dioxide, and therefore help regulate the climate, has until recently, been overlooked in assessments of the beneficial services they provide. In this study we incorporate updated knowledge on the potential of kelp to sequester ‘blue carbon’, and use the extensive kelp forests of the Falkland Islands as a case study to assess the value of kelp forest to society through multiple associated ecosystem services. Our analysis shows kelp forests provide a highly valuable range of direct and indirect services, which if managed correctly, will continue to benefit people, both now and in the future. The total estimated value of the Falkland Islands’ kelp system is currently equivalent to ~ £2.69 billion per year (or £3.24 million km -2 year -1 ). However, the true value of the kelp forest surrounding the Falkland Islands is likely to be higher still, given that our estimate does not account for elements such as associated scientific research, tourism, and cultural services, due to the necessary data currently being unavailable. Similarly, the full value of these highly biodiverse ecosystems in supplying habitat and food to a large range of associated species is crucial, yet extremely difficult to fully quantify. This study illustrates the importance of maintaining kelp ecosystems in a healthy state to ensure they continue to supply valuable ecological processes, functional roles, and ecosystem services, including their overlooked role as significant long-term carbon sinks.